Controlled spalling and flexible integration of PZT film based on LaNiO3 buffer layer. Issue 5 (1st April 2019) - Zhang, Jing; Jia, Wei; Zhang, Qicheng; He, Jian; Niu, Xushi; Qiao, Xiaojun; Geng, Wenping; Hou, Xiaojuan; Cho, Jundong; Chou, Xiujian
Abstract: As a functional ferroelectric material, PbZr0.53 Ti0.47 O3 (PZT) film is widely used in many electronic devices. However, with the rapid development of intelligent terminal, traditional PZT device cannot meet the demand for flexible wearable devices. In this work, a high-quality flexible PZT film is fabricated by the controlled spalling technology (CST) for the first time, which is novel, simple and cost-efficient. LaNiO3 (LNO) film by sol-gel process is used as the buffer layer for the PZT film growth due to good lattice match and low cost. The PZT film on silicon substrate is successfully transferred onto a flexible one by electroplating Ni stressor layer. LNO buffer layer thickness has an important influence on the spalled silicon depth and Ni stressor layer thickness during the spalling process. The exfoliated PZT film based on sandwich capacitor structure Au/PZT/Au with an area of 1 cm 2 exhibits good ferroelectric properties under different mechanical deformation. Moreover, the ferroelectric response of flexible PZT film does not show obvious deterioration after repeated operation cycles. Therefore, the flexible PZT thin film has a good application prospect on wearable ferroelectric microelectronics.